Catastrophic musculoskeletal injuries in thoroughbred racehorses in Uruguay, 2011-2017 - Bimson, N. H.; Morrice-West, A. V.; Wong, A. S. M.; Hitchens, P. L.; Rocca, M. R.; Whitton, R. C. (Journal of Equine Veterinary Science, 2022)
Catastrophic musculoskeletal injuries (CMI) pose a major welfare concern to horses and their riders, yet limited data are available describing their occurrence in South America. Using a retrospective cohort and case-control design, the objective of the study was to determine the incidence of CMI for Thoroughbreds in training and racing, and associated horse-level risk factors in Uruguay. Seventy-seven Thoroughbreds sustained a CMI, 37 of which were age- and sex-matched to 111 control horses in the same race. Training and racing data from 2011 to 2017 were collected. Incidence of race day CMI per 1,000 race starts and training CMI incidence per 100 horse months were calculated using Poisson regression. Univariable logistic regression was used to assess relationships between race history and occurrence of CMI by fracture location, and multivariable for all fracture locations. Overall race day incidence of CMI was 0.42 per 1,000 race starts (95% CI 0.29, 0.60). The incidence of CMI in training was 0.059 per 100 horse months. Twenty-nine percent (22/77) of horses that sustained a CMI had not raced prior. Most fractures were of the forelimbs (80.3%). There were 32 (41.6%) distal and 39 (50.6%) proximal limb fractures. The risk of CMI was greater for horses with fewer places (P = .001), and greater time between the previous race and the race in which CMI occurred (P = .020). The rate of race day CMI was low, despite Uruguay being a racing jurisdiction with policies and risk factors associated with greater CMI rates compared to other jurisdictions. Lightly raced horses with long periods since their previous race start should be monitored closely.